Dampak Permainan Estafet Bola pada Pembelajaran PJOK untuk Meningkatkan Motivasi Belajar Siswa Kelas 7 di SMPN 13 Surabaya - M. Zulfikar Alfanthoriq; Andhega Wijaya; Agus Suparno (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
The purpose of this class action research is to increase the motivation of grade 9 students at SMPN 13 Surabaya to learn by adding a small toxic ball game to the Physical Education, Sports, and Health (PJOK) lessons. This research utilizes a two-cycle PTK design consisting of planning, implementation, observation, and reflection. 32 grade 7 students were the subjects of the study. To collect data, observations, interviews, and questionnaires about learning motivation are used. The results showed that students' learning motivation increased significantly; By the end of the second cycle, the average score of students increased by 28%. ball relay games have been shown to be successful in increasing students' active participation and creating a fun learning environment. According to this study, ball relay games into PJOK learning can be an effective approach to increase students' desire to learn in high school.